Experimental Fracture Model versus Osteotomy Model in Metacarpal Bone Plate Fixation. (17th October 2011) - Ochman, S.; Vordemvenne, T.; Paletta, J.; Raschke, M. J.; Meffert, R. H.; Doht, S.
Abstract : Introduction . Osteotomy or fracture models can be used to evaluate mechanical properties of fixation techniques of the hand skeleton in vitro . Although many studies make use of osteotomy models, fracture models simulate the clinical situation more realistically. This study investigates monocortical and bicortical plate fixation on metacarpal bones considering both aforementioned models to decide which method is best suited to test fixation techniques. Methods . Porcine metacarpal bones (n = 40 ) were randomized into 4 groups. In groups I and II bones were fractured with a modified 3-point bending test. The intact bones represented a further control group to which the other groups after fixation were compared. In groups III and IV a standard osteotomy was carried out. Bones were fixated with plates monocortically (group I, III) and bicortically (group II, IV) and tested for failure. Results . Bones fractured at a mean maximum load of 482.8 N ±  104.8 N with a relative standard deviation (RSD) of 21.7%, mean stiffness was 122.3 ±  35 N/mm. In the fracture model, there was a significant difference (P = 0.01 ) for maximum load of monocortically and bicortically fixed bones in contrast to the osteotomy model (P = 0.9 ). Discussion . In the fracture model, because one can use the same bone for both measurements in the intact state and the bone-plate construct states, the impact of inter-individual differences is reduced. In contrast to the osteotomy model there are differences between monocortical and bicortical fixations in the fracture model. Thus simulation of the in vivo situation is better and seems to be suitable for the evaluation of mechanical properties of fixation techniques on metacarpals.